Knowledge accumulation in design-oriented research developing and communicating knowledge contributions - Barquet, Ana Paula; Wessel, Lauri; Rothe, Hannes (Lecture Notes in Computer Science (LNCS), 2017)
In this paper, we problematize a relative absence of established ways to develop and communicate knowledge contributions (KC) from Design-oriented research (DOR) within information systems. This is problematic since it hinders the potential for knowledge accumulation within the field. Thus, for communicating KC, we propose a framework, dubbed PDSA (Prescriptive, Descriptive, Situated, and Abstract). To develop KC especially from empirical data, we suggest the use of qualitative process methods. The framework is illustrated by revisiting a published DOR study. Finally, we show how the PDSA framework serves as a template to establish firm KC in DOR. In addition, we explore contributions generated from empirical data and suggest possibilities to use qualitative process methods as means to increase transparency and rigor of KC development and communication.
Keywords: Design theory; Design-oriented research; Empirical data; Knowledge contribution; Qualitative process methods